2006
DOI: 10.1111/j.1440-172x.2006.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of the measurement of ‘routine’ vital signs for adult inpatients with community‐acquired pneumonia

Abstract: More frequent vital sign evaluation does not result in a statistically significant difference in survival or the number of transfers to the intensive care unit (for progression of disease) after adjusting for age, gender, duration of intravenous antibiotics and comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Mariani et al () evaluated the benefits from routine vital signs evaluated every 6 hr versus every 8 hr or longer in 147 community‐acquired pneumonia patients admitted to the hospital between November 2000 and September 2001. Fifty‐six (39%) of the patients had vital signs recorded less often than every 8 to 12 hr, while 87 (60.8%) had vital signs recorded every 4 to 6 hr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mariani et al () evaluated the benefits from routine vital signs evaluated every 6 hr versus every 8 hr or longer in 147 community‐acquired pneumonia patients admitted to the hospital between November 2000 and September 2001. Fifty‐six (39%) of the patients had vital signs recorded less often than every 8 to 12 hr, while 87 (60.8%) had vital signs recorded every 4 to 6 hr.…”
mentioning
confidence: 99%
“…Unfortunately, the authors did not report if the nurse adherence to the policy of the frequency of postoperative vital signs was observed or had an impact on the preemptive treatment of clinical events or complications experienced by the patients. Mariani et al (2006) evaluated the benefits from routine vital signs evaluated every 6 hr versus every 8 hr or longer in 147 community-acquired pneumonia patients admitted to the hospital between November 2000 and September 2001. Fifty-six (39%) of the patients had vital signs recorded less often than every 8 to 12 hr, while 87 (60.8%) had vital signs recorded every 4 to 6 hr.…”
mentioning
confidence: 99%
“…There is little published research linking nurses' use of advanced assessment skills with traditional measurable patient outcomes such as decreased length of hospital stay and adverse events. Mariani et al (2006) found that frequent measurement of vital signs did not result in more favourable outcomes such as decreased length of stay. Recognizing when to assess and the responses made in light of assessment findings are equally important.…”
Section: Introductionmentioning
confidence: 92%
“…Mariani et al . () found that frequent measurement of vital signs did not result in more favourable outcomes such as decreased length of stay. Recognizing when to assess and the responses made in light of assessment findings are equally important.…”
Section: Introductionmentioning
confidence: 97%
“…Current triage scoring systems depend on traditional vital signs (e.g., heart rate, respiratory rate, blood pressure, temperature and pulse oximetry) and other physiological parameters. However, vital signs have not been shown to correlate well with short or long-term clinical outcomes [19].…”
Section: Introductionmentioning
confidence: 99%